Apocalyptic geographies : religion, media, and the American landscape - Tharaud, Jerome, 1980- (Book collections on Project MUSE., 2020)
"This monograph argues that Protestant evangelicals used the rise of mass print culture in the nineteenth century to produce a modern form of "sacred space" that moved beyond devotional literature to profoundly shape popular literature, art, and politics. The author places well-known works of literature and visual art-Thomas Cole's 1836 painting The Oxbow, Harriet Beecher Stowe's Uncle Tom's Cabin, Henry David Thoreau's Walden, among others-into new contexts, showing the revelatory nature they contained for religious audiences. As the author demonstrates, the antebellum landscape meant more than physical territory to be conquered or new markets to be exploited: the land itself represented intense spiritual longing and struggle, a spiritual medium through which many Americans looked to see the state of their souls and the fate of the world unveiled"--